2004
DOI: 10.1200/jco.2004.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Factors Influence Bladder Cancer Outcomes: A Cooperative Group Report

Abstract: Surgical factors influence bladder cancer outcomes after cystectomy, after adjustment for pathologic factors and neoadjuvant chemotherapy usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
311
4
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(351 citation statements)
references
References 9 publications
17
311
4
19
Order By: Relevance
“…However, there are variations in outcome, even among high-volume, experienced surgeons, suggesting that surgical technique rather than experience may independently affect outcome. In a multi-institutional study, improved surgical quality (margin status and > ten lymph nodes obtained) significantly correlated with better survival than pathological stage, nodal status, patient age and chemotherapy status [11]. One expert panel went so far as to conclude that, to be considered 'proficient' at radical cystectomy, surgeons should perform at least ten radical cystectomies per year with a minimum of 10-14 nodes obtained [12].…”
mentioning
confidence: 99%
“…However, there are variations in outcome, even among high-volume, experienced surgeons, suggesting that surgical technique rather than experience may independently affect outcome. In a multi-institutional study, improved surgical quality (margin status and > ten lymph nodes obtained) significantly correlated with better survival than pathological stage, nodal status, patient age and chemotherapy status [11]. One expert panel went so far as to conclude that, to be considered 'proficient' at radical cystectomy, surgeons should perform at least ten radical cystectomies per year with a minimum of 10-14 nodes obtained [12].…”
mentioning
confidence: 99%
“…3 Routine performance and extent of lymph node dissection is clearly associated with survival gains in the bladder cancer literature. 10 The large majority of radical cystectomies, however, are performed with a known diagnosis of muscle invasion (stage ≥pT2), whereas 50.3% of NU specimens in the current study were for pT1 disease, and clinical staging remains a significant preoperative challenge. Previous studies have found from 0-6% node-positivity in T1 disease, compared with 24% to 35% for T3 disease.…”
mentioning
confidence: 73%
“…It is also, for example, well known that surgical technique has a major impact on outcome in bladder cancer and therefore a nomogram based on a study population from centers of excellence may not be applicable outside these centers [2].…”
Section: Preoperative Assessment Of Pelvic Lymph Nodes Nomogramsmentioning
confidence: 99%